Rapid-deployment aortic valve replacement for patients with bicuspid aortic valve: a single-centre experience. (24th January 2022) - Coti, Iuliana; Werner, Paul; Kaider, Alexandra; Mach, Markus; Kocher, Alfred; Laufer, Guenther; Andreas, Martin
Abstract: OBJECTIVES: The benefit of rapid-deployment aortic valve replacement (RD-AVR) in patients with a bicuspid aortic valve (BAV) is controversial due to aortic root asymmetry and potential increased risk for valve dislocation and paravalvular leak. This study aimed to analyse the outcomes of surgical aortic valve replacement with a rapid-deployment bioprosthesis in patients with a BAV. METHODS: Between May 2010 and December 2020, all consecutive patients who underwent RD-AVR at the Medical University of Vienna were included in our institutional database. Assessment of preoperative characteristics, operative outcomes, long-term survival and clinical events was performed. The outcomes of patients presenting with a native BAV were compared with a control group of patients with native tricuspid valve (TAV); reoperative aortic valve replacements were excluded. RESULTS: Out of 816 patients, who underwent RD-AVR at our institution, 107 patients with a BAV, mean age 68 (standard deviation: 8) years, were compared with a control group of 690 patients with a TAV, mean age 74 (standard deviation: 7) years; patients presenting with a BAV were significantly younger than patients with a TAV ( P < 0.001). Concomitant procedures were performed in 44 (41.1%) patients in the BAV group and in 339 (49.1%) patients in the TAV group ( P = 0.123); surgery of the ascending aorta was necessary in 24 (22.4%) in the BAV group, compared with 29 (4.2%) in the control group ( P < 0.001). The 5-year cumulative incidence of moderate-to-severe paravalvular regurgitation in the BAV group was 10.7% [95% confidence interval (CI): 4.2–20.7%] and 3.9% (95% CI: 2.4–6.1%) in the TAV group ( P = 0.057). Reoperation with valve explantation due to non-structural valve dysfunction at 5 years was 2.8% (95% CI: 0.5–8.8%) in the BAV group, compared to 1.9% (95% CI: 1.0–3.2%) in the TAV cohort ( P = 0.89). The overall long-term survival rate in the BAV group was 92% (95% CI: 81–97%) at 5 years and 88% (95% CI: 73–95%), at 10 years, significantly better compared to the TAV group (log-rank test P = 0.002). CONCLUSIONS: RD-AVR can be performed in patients with a BAV with convincingly medical outcomes. However, a trend to increased frequency of moderate–severe paravalvular regurgitation was observed at long-term follow-up. Consequently, a different surgical approach, compared to tricuspid valves, with distinctly specific technical- and anatomical considerations and requirements, is recommended. Abstract : Bicuspid aortic valve (BAV) is the most common congenital heart valve disease, described in 1–2% of the general population [1].